TRANSFORMASI PENDIDIKAN ERA ORDE BARU: KEBIJAKAN DAN REALITAS PELAKSANAANNYA (1967 – 1990) - Khaeruddin Khaeruddin (Universitas Veteran Bangun Nusantara, 2024)
In the New Order era in Indonesia (1967-1998), the government implemented various policies to improve the quality and access to education. However, there is a discrepancy between the policies announced and the reality of their implementation in the field. The main problems faced include unequal access to education, low quality of education, and lack of adequate educational facilities and infrastructure. This study aims to analyze the transformation of education in Indonesia during the New Order era, from 1967 to 1998. The main focus is on the education policies implemented by the government and the reality of their implementation in the field. This study also evaluates the impact of this policy on the quality of education and equal access to education for all levels of society. This research uses a qualitative approach method with literature review. Data was collected from various related journal sources, articles and books. The research results show that although there have been some achievements in terms of increasing access to education, many of the policies implemented have focused more on political control than improving the quality of education. The reality of policy implementation is often not in line with the initial objectives, resulting in various problems such as lack of facilities, low quality of teaching, and educational inequality. This research provides insight into the complexity of educational transformation in the New Order era and its implications for the development of education in Indonesia.